El poroto chaucha Phaseolus vulgaris L. en la Argentina: Historia y situacion actual - Granval de Millan, N. (International Center for Tropical Agriculture, 1987)
A brief historic and statistic review of snap bean use as staple in Argentina is presented. A detailed analysis of the 4 major producing areas (Buenos Aires, Tucuman, Mendoza, and Santa Fe) is included along with a diagram with information on plant habit, or pod shape and color of the more frequently used cv. in Argentina. Snap bean destination and production prices are analyzed. The crop's main diseases and pests are listed as well as the research projects being carried out in the country. (CIAT)